Filling gaps in the southern range of the Endangered Chacoan Peccary, Parachoerus wagneri (Rusconi, 1930) (Artiodactyla, Tayassuidae), in Argentina - Matias Wajner; Francis Merlo; Daihana Argibay; Fernando Zamudio (Check List)
New records of the Endangered Parachoerus wagneri (Rusconi, 1930) are reported in northwestern Córdoba and south Santiago del Estero, Argentina. These records were obtained through interviews, confirmed with photographical evidence provided by the interviewees, and trail camera surveys. These findings confirm the presence of this species in strategic areas of its distribution and provide evidence of potential connection between northern and southern populations in Argentina. Participatory sampling is proving to be an essential tool for gathering high quality information in these areas, thus has become crucial in obtaining records and clarifying the distribution of P. wagneri.